Employability of engineering graduates in Nepal: employers’ perspectives - Sharma, Amrita (Journal of Management and Development Studies, 2023)
A huge number of graduates are seeking employment opportunities, whereas employers hardly get the suitable employees with the set of skills and competencies that they are looking for. In this context, this paper highlights the employers' perspectives towards employability, especially on the part of engineering graduates in Nepal. To meet the purpose of this paper, 'single case study' research design was adopted. The employers from private companies who employed engineers were interviewed to obtain their perspectives and/or opinions. The employers perceived that the proactiveness of the graduates along with their practical and enterprising skills as well as learning aptitudes were important as a part of employability. Current examination and evaluation systems in the engineering colleges do not exactly help the students in equipping them with those skills. They are rather dependent upon memorization creating an adverse and undesired effect to their employability. This paper reveals that all the expectations of the employers may not be fulfilled; however, the ideas and recommendations derived from the study on improving employability can bridge the gaps between the graduate’s academic performance and the employers’ expectations. Social and cultural environments also contribute to building such skills and attributes among the engineering graduates. Only having academic degree is not a gateway to the job markets in the present scenario of the country. The paper concludes that, in the perspective of the employers, the engineering education must integrate important practical skills into the academic courses in order to make the graduates more employable.